2016
DOI: 10.1080/15592324.2015.1071004
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect ofPseudomonas putidaandBacillus amyloliquefaciensameliorates drought stress in chickpea (Cicer arietinumL.)

Abstract: Two plant growth promoting rhizobacteria (PGPR) Pseudomonas putida NBRIRA and Bacillus amyloliquefaciens NBRISN13 with ability to tolerate abiotic stress along with multiple PGP traits like ACC deaminase activity, minerals solubilisation, hormones production, biofilm formation, siderophore activity were evaluated for their synergistic effect to ameliorate drought stress in chickpea. Earlier we have reported both the strains individually for their PGP attributes and stress amelioration in host plants. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(86 citation statements)
references
References 40 publications
(45 reference statements)
5
73
0
2
Order By: Relevance
“…Usually, the use of a consortium for plant inoculants guarantees the highest plant growth promotion with regard to single bacterium inoculation, due to the synergistic effect of the PGP properties present in the different strains (for recent examples see, Kumar et al . , ).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the use of a consortium for plant inoculants guarantees the highest plant growth promotion with regard to single bacterium inoculation, due to the synergistic effect of the PGP properties present in the different strains (for recent examples see, Kumar et al . , ).…”
Section: Discussionmentioning
confidence: 99%
“…A literature survey revealed an increasing number of examples where plant inoculation with compatible strains' mixtures of P. fluorescens and plant mutualistic bacteria (Sundaramoorthy and Balabaskar, 2012;Sundaramoorthy and Balabaskar, 2013;Rathi et al, 2015;Kumar et al, 2016;Sharma et al, 2018) or benefi cial fungi including species of Trichoderma (Thilagavathi et al, 2007, Jain et al, 2012Singh et al, 2013aSingh et al, , 2013bSingh et al, , 2014Ruano-Rosa et al, 2014;Thakkar and Saraf, 2015;Chemelrotit et al, 2017;Patel et al, 2017;Yadav et al, 2017;Jambhulkar et al, 2018), Beauveria (Karthiba et al, 2010;Senthilraja et al, 2013), Pochonia (Siddiqui et al, 2003) and Clonostachys (Karlsson et al, 2015) showed better results than inoculation with individual strains or control treatment, under controlled and fi eld conditions. Furthermore, co-inoculation of specifi c Pseudomonas strains that function as mycorrhiza helper bacteria (MHB) in combination with various arbuscular mucorrhiza fungi (AMF) promoted the growth of maize plants in fi eld conditions better than single AM inoculation (Berta et al, 2014).…”
Section: Pseudomonas-based Multistrain Mixturesmentioning
confidence: 99%
“…Pesticides used in this study were Carbendazim (Car), Glyphosate (Gly) and Imidacloprid (Imi). Earlier we have performed in vitro PGP traits evaluation of both the bacterium and their synergistic effect for drought amelioration in chickpea (Kumar et al 2016).…”
Section: Methodsmentioning
confidence: 99%